2023
DOI: 10.1097/md.0000000000035716
|View full text |Cite
|
Sign up to set email alerts
|

Infection with COVID-19 is a risk factor for poor prognosis in patients with intracranial hemorrhage: A prospective observational cohort study

Jia Wang,
Jin Chen

Abstract: This research aimed to explore the COVID-19 infection in the prognosis of patients with intracerebral hemorrhage (ICH), as well as analyzed the risk factors of the poor prognosis. This present prospective observational cohort study enrolled 136 patients with ICH who were admitted in our hospital during May 2020 to July 2022. The diagnosis of COVID-19 was confirmed by reverse transcriptase polymerase chain reaction. All patients were collected demographic and clinical data and were followed up for 3 months, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For many neurosurgical diseases, the duration of treatment has been significantly reduced due to better maintenance of health services during the COVID-19 pandemic, and life care has been improved for critically ill patients and those requiring recovery [ 8 ], but the impact of COVID-19 on overall survival has varied. Some patients did not have a significant influence on their survival and prognosis due to the COVID-19 pandemic [ 9 ], but it has also been reported that COVID-19 infection is a risk factor for poor prognosis of some craniocerebral diseases [ 10 , 11 ]. Most of the above data are based on individual cases to broadly analyze the influence of COVID-19 on neurosurgical diseases, which is neither universal nor comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…For many neurosurgical diseases, the duration of treatment has been significantly reduced due to better maintenance of health services during the COVID-19 pandemic, and life care has been improved for critically ill patients and those requiring recovery [ 8 ], but the impact of COVID-19 on overall survival has varied. Some patients did not have a significant influence on their survival and prognosis due to the COVID-19 pandemic [ 9 ], but it has also been reported that COVID-19 infection is a risk factor for poor prognosis of some craniocerebral diseases [ 10 , 11 ]. Most of the above data are based on individual cases to broadly analyze the influence of COVID-19 on neurosurgical diseases, which is neither universal nor comprehensive.…”
Section: Introductionmentioning
confidence: 99%